2008
DOI: 10.1038/sj.jid.5701169
|View full text |Cite
|
Sign up to set email alerts
|

Efalizumab Therapy for Atopic Dermatitis Causes Marked Increases in Circulating Effector Memory CD4+ T Cells That Express Cutaneous Lymphocyte Antigen

Abstract: Efalizumab is an mAb directed against CD11a, a molecule involved in T-cell activation and extravasation from blood into tissue. Ten patients with severe atopic dermatitis were treated with efalizumab for 84 days, and peripheral blood mononuclear cells were analyzed for expression of activation and adhesion markers. Efalizumab treatment led to decreases in CD11a mean fluorescence intensity (MFI) on naive, central memory, and effector memory CD4+ and CD8+ T cell subsets. MFI for CD18 was decreased in both CD4+ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…141,155 Efalizumab and alefacept are effective in patients with psoriasis because they interfere with receptor-ligand interactions that activate T cells (eg, lymphocyte function-associated antigen 1-intercellular adhesion molecule 1 and lymphocyte function-associated antigen 3-CD2, respectively), but little is known about their mechanisms in patients with AD; they are thought to nonspecifically deplete T cells in the skin. 141,[155][156][157] Although the role of IgE in the pathogenesis of AD is not clear, omalizumab, an mAb against IgE, has been tested. Although it is effective in treating patients with asthma, omalizumab was not observed to have effects in patients with AD, despite its ability to downregulate FceRI on DCs.…”
Section: Experimental Therapeuticsmentioning
confidence: 99%
“…141,155 Efalizumab and alefacept are effective in patients with psoriasis because they interfere with receptor-ligand interactions that activate T cells (eg, lymphocyte function-associated antigen 1-intercellular adhesion molecule 1 and lymphocyte function-associated antigen 3-CD2, respectively), but little is known about their mechanisms in patients with AD; they are thought to nonspecifically deplete T cells in the skin. 141,[155][156][157] Although the role of IgE in the pathogenesis of AD is not clear, omalizumab, an mAb against IgE, has been tested. Although it is effective in treating patients with asthma, omalizumab was not observed to have effects in patients with AD, despite its ability to downregulate FceRI on DCs.…”
Section: Experimental Therapeuticsmentioning
confidence: 99%
“…*Po0.05. of cells out of the blood (Jullien et al, 2004;Harper et al, 2008). Interestingly, we observed that intravenous administration of LtxA to a non-human primate resulted in an initial drop in WBC counts, followed by an increase in circulating WBCs within 24 hours .…”
Section: Discussionmentioning
confidence: 82%
“…The receptor for LtxA, LFA-1, has been previously validated as an effective target for treatment of psoriasis in both animal models (Zeigler et al, 2001) and humans (Jullien et al, 2004;Harper et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical studies of efalizumab, the results showed that efalizumab can induce a marked but reversible increase in peripheral lymphocytes in psoriasis patients [23][24][25] . Both populations of CD4 + and CD8 + T cells in the peripheral blood increased, with the largest increase observed in memory CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%